Salinity gradients alter root-zone soil microbiome structure and nitrogen-related functional potential in alfalfa (Medicago sativa L.): a pot experiment - Lv, Mingzi; Tian, Delong; Wang, Guoshuai; Hou, Chenli; Fan, Ting; Li, Weiping (Frontiers in Plant Science, 2026)
IntroductionSoil salinization constrains agricultural sustainability in arid and semi-arid regions. This study examined integrated soil–plant–microbe responses of alfalfa (Medicago sativa L.) to a salinity gradient.MethodsA pot experiment was conducted with control, low-, and moderate-salinity treatments. Root-zone soil and plants were sampled to measure soil EC, pH, and inorganic nitrogen forms, and to assess plant growth traits. Shotgun metagenomics was used to characterize microbial community composition and metagenome-inferred functional potential.ResultsSalinity increased soil EC and pH and altered inorganic nitrogen forms, with higher NO3--N under moderate salinity and lower NH4+-N under salinity compared with the control. Plant height peaked under low salinity, whereas fresh and dry biomass decreased under both salinity treatments. Microbial β-diversity differed among treatments, while α-diversity showed limited responses. Functional annotations indicated treatment-associated trends in nitrogen- and stress-related categories and KEGG level 3 pathways; however, most differences were not significant after FDR correction.DiscussionThis integrative root-zone assessment links salinity-driven soil chemistry changes with alfalfa performance and suggests coordinated shifts in soil chemistry, microbiome structure, and plant growth under salinity stress.